Minor’s Test: Objective Demonstration of Horner’s Syndrome - Sriraam, Laya Manasa (Indian J Otolaryngol Head Neck Surg, 2015)
To highlight the Minor’s test, which is useful in demonstrating anhidrosis of Horner’s syndrome. A 39 year old female presented to us with a slow growing neck swelling which was provisionally diagnosed as a probable case of cervical sympathetic chain (CSC) Schwannoma. Intra operatively, the mass was found arising from the CSC which was sacrificed. Post operatively, Horner’s syndrome was expected, but was difficult to demonstrate clinically. On performing the Minor’s test, the presence of anhidrosis, and thus Horner’s syndrome was confirmed. Minor’s test is a simple objective test to demonstrate Horner’s syndrome, especially because diagnosis from the eye signs can be difficult.